Overcoming barriers: a grounded theory of the experience of professionals working with justice-involved adolescents who use substances - Isabel M. Herrera-Sánchez; Samuel Rueda-Méndez; Violeta Luque-Ribelles (Humanities & Social Sciences Communications)
Abstract Adolescents involved in the juvenile justice system are particularly vulnerable to the effects of psychoactive substance use. Various studies have explored interventions from the perspective of professionals who seek strategies to meet their specific needs. This study aims to develop a substantive theory based on the experiences of professionals working in outpatient treatment centres, using a convenience sample of 20 interdisciplinary professionals. Semi-structured interviews were conducted and analysed according to Grounded Theory, identifying a basic social psychological process termed ‘overcoming barriers’, which includes four categories: reflectivity, identifying emotions, influence, and redefining results. Additionally, a basic social structural process was identified, consisting of six categories: succession, normalization, diversification, interrelation, openness, and adaptation. Three stages were established to describe the sequence in which these processes progress. The discussion focuses on analysing substance use from an ecological perspective, considering the diversity of profiles of justice-involved adolescents and best practices in professional decision-making.